Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1590/s0100-69912006000100009
|View full text |Cite
|
Sign up to set email alerts
|

Obstrução gastrointestinal por fitobezoar na cirurgia bariátrica

Abstract: RESUMO: Objetivo: O objetivo do presente estudo foi avaliar o quadro clínico, a incidência, os fatores predisponentes e a evolução de pacientes com fitobezoar após Gastroplastia Vertical e Y de Roux. Método: No período de Novembro de 1997 à Janeiro de 2004, foram realizadas 512 operações para o tratamento da Obesidade mórbida, seguindo a técnica proposta por Fobi/Capella (Septação gástrica com reconstituição em Y de Roux Proximal). Em dez pacientes foram identificados fitobezoar. Resultados: A incidência de fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
1
1
1
Order By: Relevance
“…Studies in the literature report ulcers occurrence in 1% to 5% of cases, however, no case of ulcer was found in the present study (14)(15)(16)(17) . The present study has found one case of bezoar (2.4%), while the literature reports a 1.9% incidence (19) . Also, one case of enterocutaneous fistula was found, while Capella et al report a low incidence of this complication (20) .…”
Section: Discussioncontrasting
confidence: 45%
“…Studies in the literature report ulcers occurrence in 1% to 5% of cases, however, no case of ulcer was found in the present study (14)(15)(16)(17) . The present study has found one case of bezoar (2.4%), while the literature reports a 1.9% incidence (19) . Also, one case of enterocutaneous fistula was found, while Capella et al report a low incidence of this complication (20) .…”
Section: Discussioncontrasting
confidence: 45%
“…No artigo de Ferraz et al 37 ralizado em 2006, os autores tinham por objetivo avaliar o quadro clínico, a incidência, os fatores predisponentes e a evolução dos pacientes com fitobezoar (tipo de fibra vegetal, geralmente formada por sementes, raízes, Figura 1. A) Fitobezoar fixo ao fio de sutura; B) Imagem aproximada fitobezoar fixo ao fio.…”
Section: Parâmetros Clínicosunclassified
“…Individuals with a greater propensity to develop phytobezoars include not only vegetarians but also individuals who do not chew their food well, those with impaired gastric motility, and those with hypochlorhydria, as well as those who have undergone gastrectomy. A history of gastric surgery is a risk factor because it reduces the surface area of the stomach and acid secretions, causing inadequate digestion and allowing larger masses of agglomerated material to pass into the small intestine ( 1 - 3 ) . Phytobezoars can also occur in patients who have had bariatric surgery.…”
mentioning
confidence: 99%